2020
DOI: 10.1111/ele.13474
|View full text |Cite
|
Sign up to set email alerts
|

Alpine grassland plants grow earlier and faster but biomass remains unchanged over 35 years of climate change

Abstract: Satellite data indicate significant advancement in alpine spring phenology over decades of climate warming, but corresponding field evidence is scarce. It is also unknown whether this advancement results from an earlier shift of phenological events, or enhancement of plant growth under unchanged phenological pattern. By analyzing a 35‐year dataset of seasonal biomass dynamics of a Tibetan alpine grassland, we show that climate change promoted both earlier phenology and faster growth, without changing annual bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
79
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 144 publications
(125 citation statements)
references
References 58 publications
13
79
0
Order By: Relevance
“…It indicates that earlier spring phenology could aggravate the suppression of carbon assimilation in autumn in drier areas. The negative lagged effect of earlier BGS on the autumn NPP was consistent with a field-measured result on the TP [53]. Previous studies also reported a similar linkage between spring phenology and ecosystem productivity in the subsequent seasons for subalpine forests and temperate grasslands [25,54].…”
Section: Direct and Lagged Effects Of Spring Phenology On Nppsupporting
confidence: 88%
“…It indicates that earlier spring phenology could aggravate the suppression of carbon assimilation in autumn in drier areas. The negative lagged effect of earlier BGS on the autumn NPP was consistent with a field-measured result on the TP [53]. Previous studies also reported a similar linkage between spring phenology and ecosystem productivity in the subsequent seasons for subalpine forests and temperate grasslands [25,54].…”
Section: Direct and Lagged Effects Of Spring Phenology On Nppsupporting
confidence: 88%
“…6). This demonstrates the possible negative effect of temperature rising on AGB that has been widely reported (De Boeck et al, 2008;Wang et al, 2020), particularly in the arid and semi-arid ecosystems (Ma et al, 2010b). This harmful influence of warming on AGB is explainable.…”
Section: Discussionsupporting
confidence: 60%
“…Dynamics of grassland biomass are driven by complex interactions among a series of environmental attributes, among which climate is one of the most predominant drivers (De Boeck et al, 2008;Wang et al, 2020). The magnitudes and directions of climate change effects on AGB can vary across different local environments as well.…”
mentioning
confidence: 99%
“…The average altitude of TP is >4000m, and MAT is <0°C, the highest monthly average temperature in <10°C, and the MAP is 20–487mm [ 23 ]. There are three grassland types, namely, alpine meadow, alpine grassland, and alpine desert from southeast to northwest [ 24 ].…”
Section: Methodsmentioning
confidence: 99%